1991
DOI: 10.1021/cm00017a023
|View full text |Cite
|
Sign up to set email alerts
|

Third-order optical nonlinearities of model compounds containing benzobisthiazole, benzobisoxazole, and benzbisimidazole units

Abstract: As part of a continuing study, a series of highly conjugated aromatic benzobisthiazole, benzobisoxazole, and N,N-diphenylbenzbisimidazole model compounds were synthesized, and their third-order nonlinear optical properties investigated by using subpicosecond degenerate four-wave mixing. Measurementa were made at 602 nm on THF solutions, vacuum-deposited films, or melt-quenched films. In all but one material, the third-order effect was determined to be instantaneous within the employed temporal resolution, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…A comparison of the results for three symmetrically substituted diacetylenes 3TNDA, 1DNDA and 3DQDA at 810 nm shows that the aryl substituents containing a heteroatom such as N and S produce large transition dipole moment 01 and hence higher nonlinearity. This is consistent with the recent observations in oligomers of conjugated rigid-rod polymer PBO and PBZT 34,35 where the sulphur heteroatom substitution enhanced the nonlinearity by a factor of 3. From our studies, it seems that N heterocyclic substitution is more effective than the S heterocyclic substitution for achieving higher nonlinearity.…”
Section: Resultssupporting
confidence: 93%
“…A comparison of the results for three symmetrically substituted diacetylenes 3TNDA, 1DNDA and 3DQDA at 810 nm shows that the aryl substituents containing a heteroatom such as N and S produce large transition dipole moment 01 and hence higher nonlinearity. This is consistent with the recent observations in oligomers of conjugated rigid-rod polymer PBO and PBZT 34,35 where the sulphur heteroatom substitution enhanced the nonlinearity by a factor of 3. From our studies, it seems that N heterocyclic substitution is more effective than the S heterocyclic substitution for achieving higher nonlinearity.…”
Section: Resultssupporting
confidence: 93%
“…They have concluded that inclusion of sulfur as heteroatom in the π-conjugated system might enhance the nonlinearity, due to either the participation of empty d orbitals or the establishment of steric interactions between each unit. Sulfur-containing aromatic links such as thiophene were found to impart much more positive variations of the NLO properties than those aromatic systems containing nitrogen and/or oxygen atoms. , …”
Section: Organic Materialsmentioning
confidence: 98%
“…Additionally the empty d orbitals of the sulfur atom can contribute to the molecular p-orbitals decreasing the energy of the p-p* transition. 5,21 Based on the UPS data it appears that changing the position of the oxygen atoms destabilizes the HOMO level, while slightly stabilizing the LUMO level. Whereas exchanging the oxygen atoms for sulfur stabilizes both the HOMO and LUMO levels.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…These electron-deficient heterocycles are known for improving the charge transport, photoluminescence, and third-order nonlinear optical properties of materials containing them. [4][5][6] Recently, new materials based on a donor-acceptordonor (D-A-D) triad composed of a benzobisthiazole ring sandwiched between two alkylthiophenes have been reported. [7][8][9][10] Organic field effect transistors using small molecules based on this D-A-D triad exhibited excellent hole mobility as a result of the materials' high crystalinity.…”
Section: Introductionmentioning
confidence: 99%